The impact of preeclampsia in pregnancy - Manaj, Aferdita (CIC Edizioni Internazionali, 2011)
Objective. To observe the influence of preeclampsia during pregnancy. Materials and methods. 5711 patient’s records of the year 2008 and 6188 patient’s records of the year 2009 of Obstetric/Gynecologic hospital ‘Queen Geraldina’ have been consulted. The age of women that we studied in 2008 was between 23-35 and in 2009 was be-tween 25-34 years old. We have made a careful diagnose of inducted hypertension of pregnancy and preeclampsia. Results. The incidence of preeclampsia in the population was 4.1% (n =238) in 2008 and 3.1% (n=192) in 2009.The incidence of the cases that developed from preeclampsia to eclampsia were respectively 1.6% (n=4) and 1.5% (n=3) on 2009. Babies which have preeclamptic mothers were preterm in 13% (n=31) of cases, and 14.5% (n=28) of which have severe hypotrophia vs. 10% (n=24) and 11% (n=21) severe hypotrophia in 2009. Babies mortality on the preeclamptic population were respectively 8% (n=19) and 7.8% (n=15). Conclusions. From the survey resulted that patients diagnosed with preeclampsia manifested on a high rate hypertension and proteinuria. Prematurity, severe hypotrophy and baby’s mortality were the major complications of preeclampsia. Women with preeclampsia were especially the youngest.